Epoxy resin adhesive based on anti-settling heat conduction network and preparation method thereof
Patent Information
- Application Number
- CN202611128146.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-09
AI Technical Summary
[0003]针对上述技术难题,本发明提供了一种基于防沉降导热网络的环氧树脂(EP)胶粘剂及其制备方法,旨在解决现有导热胶粘剂长期储存稳定性差、导热系数低、填料分散均匀性差、工艺复杂等技术难题,该方法通过多壁碳纳米管(MWCNTs)与芳纶纳米纤维(ANFs)在环氧树脂基体中自构筑形成三维网状结构,该结构一方面对填料形成稳定的物理锁定,实现其在树脂体系中的均匀分散,有效抑制其沉降;另一方面依托MWCNTs的高长径比与ANFs的桥连作用,二者相互搭接形成连续、低热阻的高效通路,从而辅助外加导热填料构建丰富的导热网络,有效提升胶粘剂的导热效率,为制备高导热胶粘剂提供了一条新的技术途径
本发明方法利用芳纶纳米纤维与环氧树脂之间良好的相容性使得MWCNTs/ANFs在环氧树脂内部构建MWCNTs/ANFs/EP三维网络(图1),依靠芳纶纳米纤维的支撑作用,防止导热填料的沉降及分布不均,从而提高复合材料的导热性能。其中,MWCNTs/ANFs得以在环氧树脂里形成三维网络的理由如下:(1)芳纶纳米纤维呈一维纳米纤维状结构,其高长径比在分散过程中易相互搭接、缠绕,形成物理上的三维网络结构。(2)芳纶纳米纤维不仅表面含有丰富的酰胺键(-CONH-)等极性基团和芳香族苯环结构,可以与环氧树脂分子链上的环氧基、羟基(-OH)和醚键(-O-)之间通过氢键、偶极-偶极相互作用等形成强分子间作用力,芳纶纳米纤维之间也能通过极强的氢键和芳香环结构之间的π-π堆积相互作用。多种分子间的作用力能够将纤维与纤维之间、纤维与树脂之间松散的物理搭接“焊接”成一个坚固、稳定的三维网络。
Smart Images

Figure CN122878906A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of epoxy resin adhesive technology, specifically relating to a thermally conductive epoxy resin adhesive based on the synergistic effect of a flexible thermally conductive framework and thermally conductive filler of multi-walled carbon nanotubes (MWCNTs) and aramid nanofibers (ANFs), and its preparation method. Background Technology
[0002] With the rapid development of microelectronics technology towards miniaturization, integration, and high power, the heat flux density of electronic devices continues to rise. Traditional adhesives are no longer sufficient to meet the efficient heat dissipation requirements of high-power devices, and the heat accumulated during device operation cannot be dissipated in a timely manner. Currently, epoxy resins are the main matrix resins in the adhesive field. However, epoxy adhesives have extremely low intrinsic thermal conductivity, which easily leads to heat accumulation and seriously affects the operational stability and service life of electronic devices. Against this background, developing a modified epoxy adhesive with high thermal conductivity is the current mainstream research direction. Existing high thermal conductivity epoxy adhesives are mostly prepared by simple physical blending methods. This preparation method often suffers from problems such as poor filler dispersion uniformity and easy sedimentation during storage. Usually, a high filler content is required to barely form a continuous thermal conduction path. On the other hand, the process of preparing thermally conductive adhesives using prefabricated thermally conductive skeletons is complex and costly, making it difficult to achieve large-scale industrial production. Summary of the Invention
[0003] To address the aforementioned technical challenges, this invention provides an epoxy resin (EP) adhesive based on an anti-settling thermally conductive network and its preparation method. This aims to solve the technical problems of existing thermally conductive adhesives, such as poor long-term storage stability, low thermal conductivity, poor filler dispersion uniformity, and complex processes. The method utilizes multi-walled carbon nanotubes (MWCNTs) and aramid nanofibers (ANFs) to self-construct a three-dimensional network structure within an epoxy resin matrix. This structure, on the one hand, provides stable physical locking for the filler, achieving uniform dispersion in the resin system and effectively inhibiting its sedimentation; on the other hand, relying on the high aspect ratio of MWCNTs and the bridging effect of ANFs, the two interlock to form a continuous, low-thermal-resistance, high-efficiency pathway. This assists in constructing a rich thermally conductive network with the addition of external thermally conductive fillers, effectively improving the thermal conductivity of the adhesive and providing a new technical approach for preparing high thermally conductive adhesives.
[0004] This invention provides an epoxy resin adhesive based on an anti-settling thermal conductive network, the composition and raw material mass percentages of which are as follows: Epoxy resin compounds: 20.0%~31.0%; Multifunctional epoxy resin diluent 13.0%~21.0%; Hardener 6.0%~10.0%; Silane coupling agent 0.8%~1.2%; Thermally conductive fillers: 40.0%~60.0%; Aramid nanofibers: 0.01%~0.03%; Multi-walled carbon nanotubes: 0.001%~0.003%.
[0005] Preferably, the epoxy resin compound is selected from one or more of glycidyl ether epoxy resins, glycidyl amine epoxy resins, glycidyl ester epoxy resins, alicyclic epoxy resins, and linear aliphatic epoxy resins.
[0006] Preferably, the multifunctional epoxy resin diluent is selected from one or more of ethylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, trimethylolpropane triglycidyl ether, and glycerol triglycidyl ether.
[0007] Preferably, the curing agent is a latent curing agent, selected from one or more of dicyandiamide compounds and adipic acid dihydrazide.
[0008] Preferably, the silane coupling agent is selected from one or more of γ-aminopropyltriethoxysilane (KH-550), γ-glycidoxypropyltrimethoxysilane (KH-560), γ-methacryloyloxypropyltrimethoxysilane (KH-570), and γ-mercaptopropyltrimethoxysilane (KH-590).
[0009] Preferably, the aramid nanofiber substrate is selected from one or more of poly(m-phenylene isophthalamide) and poly(p-phenylene terephthalamide).
[0010] Preferably, the thermally conductive filler is selected from one or more of silicon carbide whiskers, silicon carbide particles, and boron nitride.
[0011] On the other hand, the present invention also provides a method for preparing an epoxy resin adhesive based on an anti-settling thermal conductive network, comprising the following steps: Preparation of MWCNTs / ANFs composite materials: Aramid nanofibers and multi-walled carbon nanotubes were added to a mixed system containing a strong alkaline reagent, deionized water, and a polar aprotic organic solvent (such as dimethyl sulfoxide). The mixture was stirred at 40℃~60℃ for 2h~6h to obtain a MWCNTs / ANFs mixed dispersion. Subsequently, deionized water was slowly added dropwise to the mixed dispersion to induce the co-precipitation of MWCNTs and ANFs. After filtration, the MWCNTs / ANFs composite material was obtained. During the filtration process, the solid phase was washed multiple times with a low-boiling-point, volatile polar organic cleaning agent (such as ethanol or acetone) that is miscible with the aforementioned polar aprotic organic solvent to remove residual strong alkaline reagents and polar aprotic organic solvents from the material. In the above preparation process, the distribution ratio of each component of MWCNTs / ANFs can be effectively controlled by adjusting the initial concentration of MWCNTs in the mixed dispersion and the mass of the MWCNTs / ANFs mixed dispersion.
[0012] Surface modification of filler: Prepare an ethanol-water solution, add acetic acid to adjust the pH to 4.0-4.5, place the pH-adjusted ethanol-water solution at room temperature and stir for 20-40 minutes, add silane coupling agent and continue stirring to mix evenly to form a silane coupling agent hydrolysate; weigh the thermally conductive filler and add it to the above silane coupling agent hydrolysate, and perform the following dispersion treatments in sequence: magnetic stirring for 20-40 minutes, high-speed homogenization for 15-30 minutes, and ultrasonic dispersion for 20-40 minutes, preferably magnetic stirring for 30 minutes, high-speed homogenization for 20 minutes, and ultrasonic dispersion for 40 minutes. Filter the treated dispersion and vacuum dry to obtain the surface-modified thermally conductive filler.
[0013] Preparation of thermally conductive composite material: Weigh epoxy resin compounds and multifunctional epoxy resin diluents, mix them with the prepared MWCNTs / ANFs composite material, and stir at 70℃~80℃ until homogeneous to achieve initial dispersion of MWCNTs / ANFs and remove residual solvent. Then, add the prepared surface-modified thermally conductive filler to the above mixture, ultrasonically treat to ensure uniform dispersion of the filler, and finally add curing agent and heat to cure, thus obtaining the thermally conductive epoxy composite material.
[0014] The beneficial effects of this invention are: The method of this invention utilizes the good compatibility between aramid nanofibers and epoxy resin to construct a three-dimensional network of MWCNTs / ANFs / EP within the epoxy resin. Figure 1The thermal conductivity of the composite material is improved by relying on the supporting effect of aramid nanofibers to prevent the sedimentation and uneven distribution of thermally conductive fillers. The reasons why MWCNTs / ANFs can form a three-dimensional network in epoxy resin are as follows: (1) Aramid nanofibers have a one-dimensional nanofiber structure. Their high aspect ratio makes them easy to overlap and entangle each other during dispersion, forming a physical three-dimensional network structure. (2) Aramid nanofibers not only contain abundant polar groups such as amide bonds (-CONH-) and aromatic benzene ring structures on their surface, but also form strong intermolecular forces with epoxy groups, hydroxyl groups (-OH) and ether bonds (-O-) on the epoxy resin molecular chain through hydrogen bonds, dipole-dipole interactions, etc. Aramid nanofibers can also interact with each other through extremely strong hydrogen bonds and π-π stacking interactions between aromatic ring structures. Multiple intermolecular forces can "weld" the loose physical overlap between fibers and between fibers and resin into a strong and stable three-dimensional network.
[0015] Adding MWCNTs / ANFs to epoxy resin systems can prevent the sedimentation of thermally conductive fillers and regulate the distribution of whiskers through spatial confinement effects. This guides the whiskers to oriented along network nodes, helping to form continuous, low-thermal-resistance whisker-fiber thermally conductive pathways, thus regulating the orientation of the thermally conductive fillers and effectively improving the thermal conductivity of epoxy composites. Simultaneously, MWCNTs / ANFs can also exert a synergistic effect, overlapping to form continuous, low-thermal-resistance, and highly efficient pathways, further improving the system's thermal conductivity. Furthermore, the excellent thermal stability and flame retardancy of aramid nanofibers enhance the overall performance of the epoxy composite system, expanding its application range. This invention, by introducing a MWCNTs / ANFs composite framework, offers advantages over traditional blending methods in preparing thermally conductive composites, including simple preparation, cost savings, and superior thermal conductivity, thus expanding the application range of epoxy adhesives. Attached Figure Description
[0016] Figure 1 SEM image of the cross section of the MWCNTs / ANFs / EP composite material. Detailed Implementation
[0017] The invention will be further elaborated and explained below with reference to specific experimental procedures.
[0018] Example 1 This embodiment provides an epoxy resin adhesive based on an anti-settling thermally conductive network. The epoxy resin adhesive comprises: epoxy resin compounds, multifunctional epoxy resin diluents, curing agents, silane coupling agents, thermally conductive fillers, aramid nanofibers, and multi-walled carbon nanotubes.
[0019] In this embodiment, the epoxy resin compound is a glycidyl ether epoxy resin; In this embodiment, the multifunctional epoxy resin diluent is ethylene glycol diglycidyl ether; In this embodiment, the curing agent is dicyandiamide; In this embodiment, the silane coupling agent is γ-glycidoxypropyltrimethoxysilane; In this embodiment, the thermally conductive filler is silicon carbide whiskers.
[0020] This embodiment provides a method for preparing an epoxy resin adhesive based on an anti-settling thermally conductive network: 0.5g of aramid nanofibers and 0.05g of multi-walled carbon nanotubes are added to a mixture of 0.75g of potassium hydroxide, 10mL of deionized water, and 250mL of dimethyl sulfoxide. The mixture is magnetically stirred at 50°C for 4 hours to obtain a MWCNTs / ANFs mixed dispersion of a certain concentration. 25g of the prepared mixed dispersion is taken, and deionized water is added dropwise to allow it to settle. The mixture is then vacuum filtered to obtain 0.05g of the MWCNTs / ANFs composite material. Acetone is used for washing during filtration to remove reagents such as KOH and DMSO, as well as organic solvents.
[0021] An ethanol-water solution was prepared with a deionized water to anhydrous ethanol mass ratio of 1:10. Acetic acid was added dropwise to adjust the pH to 4.0. The pH-adjusted solution was stirred at 25°C for 40 min. Then, γ-glycidoxypropyltrimethoxysilane (KH-560) was added at 2% of the mass of silicon carbide whiskers, and stirring was continued to allow for complete hydrolysis. Silicon carbide whiskers were added to the above silane hydrolysate, and the following dispersion treatments were performed in sequence: magnetic stirring for 30 min, high-speed homogenization for 20 min, and ultrasonic dispersion for 40 min. The treated dispersion was filtered and vacuum dried to obtain surface-modified silicon carbide whiskers.
[0022] 60g of glycidyl ether epoxy resin (E-51) and 40g of ethylene glycol diglycidyl ether were weighed and mixed evenly. 0.05g of the prepared MWCNTs / ANFs composite material was added to the mixture. The mixture was magnetically stirred in an 80℃ water bath for 4 hours to achieve initial dispersion of MWCNTs / ANFs and complete removal of acetone. Then, 79.4g of surface-modified silicon carbide whiskers were added, making them 40wt% of the total system. The mixture was magnetically stirred for 1 hour and ultrasonicated for 1 hour. Finally, 19g of dicyandiamide curing agent was weighed, vacuum degassed, and added to the system. The curing process involved heating at 130℃ for 1 hour and then at 140℃ for 30 minutes. The resulting high thermal conductivity epoxy adhesive was tested. Under test conditions of 25℃, the out-of-plane thermal conductivity and in-plane thermal conductivity were 1.096 W / (m²). K), 1.135W / (m K).
[0023] Comparative Example 1 The difference between this comparative example and Example 1 is that no MWCNTs / ANFs composite material was added to the epoxy resin. Under the same test conditions, the out-of-plane thermal conductivity and in-plane thermal conductivity of the obtained epoxy adhesive were 0.824 W / (m²). K), 1.117W / (m The thermal conductivity decreased by 0.272 W / (m²) compared to the out-of-plane and in-plane thermal conductivity of Example 1. K), 0.018W / (m K).
[0024] Example 2 This embodiment provides an epoxy resin adhesive based on an anti-settling thermally conductive network. The epoxy resin adhesive comprises: epoxy resin compounds, multifunctional epoxy resin diluents, curing agents, silane coupling agents, thermally conductive fillers, aramid nanofibers, and multi-walled carbon nanotubes.
[0025] In this embodiment, the epoxy resin compound is a linear aliphatic epoxy resin; In this embodiment, the multifunctional epoxy resin diluent is glycerol triglycidyl ether. In this embodiment, the curing agent is adipic acid dihydrazide; In this embodiment, the silane coupling agent is γ-aminopropyltriethoxysilane; In this embodiment, the thermally conductive filler is silicon carbide particles.
[0026] This embodiment provides a method for preparing an epoxy resin adhesive based on an anti-settling thermally conductive network: 0.5g of aramid nanofibers and 0.05g of multi-walled carbon nanotubes are added to a mixture of 0.75g of potassium hydroxide, 10mL of deionized water, and 250mL of dimethyl sulfoxide. The mixture is magnetically stirred at 50°C for 4 hours to obtain a MWCNTs / ANFs mixed dispersion of a certain concentration. 25g of the prepared mixed dispersion is taken, and deionized water is added dropwise to allow it to settle. Vacuum filtration is then performed to obtain 0.05g of the MWCNTs / ANFs composite material. Acetone is used for washing during filtration to remove reagents such as KOH and DMSO, as well as organic solvents.
[0027] An ethanol-water solution was prepared with a deionized water to anhydrous ethanol mass ratio of 1:10. Acetic acid was added dropwise to adjust the pH to 4.0. The pH-adjusted solution was stirred at 25°C for 40 min. Then, γ-glycidoxypropyltrimethoxysilane (KH-560) was added at 2% of the mass of the silicon carbide particles, and stirring was continued to allow for complete hydrolysis. Silicon carbide particles were added to the above silane hydrolysate, and the following dispersion treatments were performed in sequence: magnetic stirring for 30 min, high-speed homogenization for 20 min, and ultrasonic dispersion for 40 min. The treated dispersion was filtered and vacuum dried to obtain surface-modified silicon carbide particles.
[0028] 60g of linear aliphatic epoxy resin and 40g of glycerol triglycidyl ether were weighed and mixed evenly. 0.05g of the prepared MWCNTs / ANFs composite material was added to the mixture. The mixture was magnetically stirred in an 80℃ water bath for 4 hours to achieve initial dispersion of MWCNTs / ANFs and complete removal of acetone. Then, 178.6g of surface-modified silicon carbide particles were added, making them 60wt% of the total system. The mixture was magnetically stirred for 1 hour and ultrasonicated for 1 hour. Finally, 20g of adipic acid dihydrazide curing agent was weighed, vacuum degassed, and added to the system. The curing process involved heating at 140℃ for 2 hours and then at 150℃ for 90 minutes. The resulting high thermal conductivity epoxy adhesive was tested. Under test conditions of 25℃, the out-of-plane thermal conductivity and in-plane thermal conductivity were 1.207 W / (m²). K), 1.284W / (m K).
[0029] Comparative Example 2 The difference between this comparative example and Example 2 is that no MWCNTs / ANFs composite material was added to the epoxy resin. Under the same test conditions, the out-of-plane thermal conductivity and in-plane thermal conductivity of the obtained epoxy adhesive were 1.007 W / (m²). K), 1.123W / (m The thermal conductivity decreased by 0.2 W / (m²) compared to the out-of-plane and in-plane thermal conductivity of Example 2. K), 0.161W / (m K).
[0030] Example 3 This embodiment provides an epoxy resin adhesive based on an anti-settling thermally conductive network. The epoxy resin adhesive comprises: epoxy resin compounds, multifunctional epoxy resin diluents, curing agents, silane coupling agents, thermally conductive fillers, aramid nanofibers, and multi-walled carbon nanotubes.
[0031] In this embodiment, the epoxy resin compound is a glycidyl ester epoxy resin; In this embodiment, the multifunctional epoxy resin diluent is ethylene glycol diglycidyl ether; In this embodiment, the curing agent is dicyandiamide; In this embodiment, the silane coupling agent is γ-aminopropyltriethoxysilane; In this embodiment, the thermally conductive filler is silicon carbide whiskers or silicon carbide particles.
[0032] This embodiment provides a method for preparing an epoxy resin adhesive based on an anti-settling thermally conductive network: 0.5g of aramid nanofibers and 0.05g of multi-walled carbon nanotubes are added to a mixture of 0.75g of potassium hydroxide, 10mL of deionized water, and 250mL of dimethyl sulfoxide. The mixture is magnetically stirred at 50°C for 4 hours to obtain a MWCNTs / ANFs mixed dispersion of a certain concentration. 25g of the prepared mixed dispersion is taken, and deionized water is added dropwise to allow it to settle. Vacuum filtration is then performed to obtain 0.05g of the MWCNTs / ANFs composite material. During filtration, acetone is used to wash away reagents such as KOH and DMSO, as well as organic solvents.
[0033] An ethanol-water solution was prepared by mixing deionized water and anhydrous ethanol at a mass ratio of 1:10. Acetic acid was added dropwise to adjust the pH to 4.0. The pH-adjusted solution was then stirred at 25°C for 40 min. Subsequently, γ-aminopropyltriethoxysilane (KH-550) was added at 2% of the mass of the silicon carbide whiskers, and stirring was continued to ensure complete hydrolysis. Silicon carbide whiskers were then added to the silane hydrolysate, and the following dispersion treatments were performed sequentially: magnetic stirring for 30 min, high-speed homogenization for 20 min, and ultrasonic dispersion for 40 min. The treated dispersion was filtered and vacuum dried to obtain surface-modified silicon carbide whiskers. Surface-modified silicon carbide particles were obtained using the same process described above.
[0034] 60g of glycidyl ester epoxy resin and 40g of ethylene glycol diglycidyl ether were weighed and mixed evenly. 0.05g of the prepared MWCNTs / ANFs composite material was added to the mixture. The mixture was magnetically stirred in an 80℃ water bath for 4 hours to achieve initial dispersion of MWCNTs / ANFs and complete removal of acetone. Then, 59.5g of surface-modified silicon carbide whiskers and 119.0g of surface-modified silicon carbide particles were added, with the total filler content accounting for 60wt% of the entire system. The mixture was magnetically stirred for 1 hour and ultrasonicated for 1 hour. Finally, 19g of dicyandiamide curing agent was weighed, vacuum degassed, and added to the system. The curing process involved heating at 130℃ for 1 hour and then at 140℃ for 30 minutes. The resulting high thermal conductivity epoxy adhesive was tested. Under test conditions of 25℃, the out-of-plane thermal conductivity and in-plane thermal conductivity were 1.378 W / (m²). K), 1.504W / (m K).
[0035] Comparative Example 3 The difference between this comparative example and Example 3 is that no MWCNTs / ANFs composite material was added to the epoxy resin. Under the same test conditions, the out-of-plane thermal conductivity and in-plane thermal conductivity of the obtained epoxy adhesive were 1.199 W / (m²). K), 1.336W / (m The thermal conductivity decreased by 0.179 W / (m²) compared to the out-of-plane and in-plane thermal conductivity of Example 3. K), 0.168W / (m K).
[0036] Example 4 This embodiment provides an epoxy resin adhesive based on an anti-settling thermally conductive network. The epoxy resin adhesive comprises: epoxy resin compounds, multifunctional epoxy resin diluents, curing agents, silane coupling agents, thermally conductive fillers, aramid nanofibers, and multi-walled carbon nanotubes.
[0037] In this embodiment, the epoxy resin compound is a glycidyl ether epoxy resin; In this embodiment, the multifunctional epoxy resin diluent is ethylene glycol diglycidyl ether; In this embodiment, the curing agent is adipic acid dihydrazide; In this embodiment, the silane coupling agent is γ-mercaptopropyltrimethoxysilane; In this embodiment, the thermally conductive filler is silicon carbide particles or boron nitride.
[0038] This embodiment provides a method for preparing an epoxy resin adhesive based on an anti-settling thermally conductive network: 0.5g of aramid nanofibers and 0.05g of multi-walled carbon nanotubes are added to a mixture of 0.75g of potassium hydroxide, 10mL of deionized water, and 250mL of dimethyl sulfoxide. The mixture is magnetically stirred at 50°C for 4h to obtain a MWCNTs / ANFs mixed dispersion of a certain concentration. 25g of the above-prepared mixed dispersion is taken, and deionized water is added dropwise to allow it to settle. Then, vacuum filtration is performed to obtain 0.05g of the MWCNTs / ANFs composite material. During the filtration process, acetone is used to wash the material to remove reagents such as KOH and DMSO, as well as organic solvents.
[0039] An ethanol-water solution was prepared by mixing deionized water and anhydrous ethanol at a mass ratio of 1:10. Acetic acid was added dropwise to adjust the pH to 4.0. The pH-adjusted solution was stirred at 25°C for 40 min. γ-mercaptopropyltrimethoxysilane (KH-590) at 2% of the mass of silicon carbide particles was added, and stirring was continued to allow for complete hydrolysis. Silicon carbide particles were then added to the silane hydrolysate, and the following dispersion treatments were performed sequentially: magnetic stirring for 30 min, high-speed homogenization for 20 min, and ultrasonic dispersion for 40 min. The treated dispersion was filtered and vacuum dried to obtain surface-modified silicon carbide particles. Surface-modified boron nitride was prepared using the same process.
[0040] 60g of glycidyl ether epoxy resin (E-51) and 40g of ethylene glycol diglycidyl ether were weighed and mixed evenly. 0.05g of the prepared MWCNTs / ANFs composite material was added to the mixture. The mixture was magnetically stirred in an 80℃ water bath for 4 hours to achieve initial dispersion of MWCNTs / ANFs and complete removal of acetone. Then, 47.8g of surface-modified silicon carbide particles and 71.7g of surface-modified boron nitride were added, with the total filler content accounting for 50wt% of the entire system. The mixture was magnetically stirred for 1 hour and ultrasonicated for 1 hour. Finally, 20g of adipate dihydrazide curing agent was weighed, vacuum degassed, and added to the system. The curing process involved heating at 140℃ for 2 hours and then at 150℃ for 90 minutes. The resulting high thermal conductivity epoxy adhesive was tested. Under test conditions of 25℃, the out-of-plane thermal conductivity and in-plane thermal conductivity were 1.672 W / (m²). K), 1.814W / (m K).
[0041] Comparative Example 4 The difference between this comparative example and Example 4 is that no MWCNTs / ANFs composite material was added to the epoxy resin. Under the same test conditions, the out-of-plane thermal conductivity and in-plane thermal conductivity of the obtained epoxy adhesive were 1.424 W / (m²). K), 1.709W / (m The thermal conductivity decreased by 0.248 W / (m²) compared to the out-of-plane and in-plane thermal conductivity of Example 4. K), 0.106W / (m K).
[0042] This invention provides an epoxy resin adhesive based on an anti-settling thermally conductive network and its preparation method. It introduces aramid nanofibers and multi-walled carbon nanotubes into an epoxy matrix to form a three-dimensional network structure. This structural design can effectively prevent the thermally conductive filler from settling, assist in the formation of thermally conductive pathways, improve the thermal conductivity of the epoxy adhesive, meet the requirements of industrial mass production, and at the same time improve the service life of electronic components.
[0043] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit the scope of protection of the present invention. Any modifications or equivalent substitutions made without departing from the essence and scope of the technical solutions of the present invention shall fall within the scope of protection of the present invention.
Claims
1. An epoxy resin adhesive based on an anti-settling thermal conductive network, characterized in that, Its components and raw material mass percentages are as follows: Epoxy resin compounds: 20.0%~31.0%; Multifunctional epoxy resin diluent 13.0%~21.0%; Hardener 6.0%~10.0%; Silane coupling agent 0.8%~1.2%; Thermally conductive fillers: 40.0%~60.0%; Aramid nanofibers: 0.01%~0.03%; Multi-walled carbon nanotubes: 0.001%~0.003%.
2. The epoxy resin adhesive based on an anti-settling thermal conductive network according to claim 1, characterized in that, The epoxy resin compound is selected from any one or more of glycidyl ether epoxy resins, glycidyl amine epoxy resins, glycidyl ester epoxy resins, alicyclic epoxy resins, and linear aliphatic epoxy resins.
3. The epoxy resin adhesive based on an anti-settling thermal conductive network according to claim 1, characterized in that, The multifunctional epoxy resin diluent is selected from one or more of ethylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, trimethylolpropane triglycidyl ether, and glycerol triglycidyl ether.
4. The epoxy resin adhesive based on an anti-settling thermal conductive network according to claim 1, characterized in that, The curing agent is a latent curing agent, selected from one or more of dicyandiamide compounds and adipic acid dihydrazide.
5. The epoxy resin adhesive based on an anti-settling thermal conductive network according to claim 1, characterized in that, The silane coupling agent is selected from any one or more of γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-methacryloyloxypropyltrimethoxysilane, and γ-mercaptopropyltrimethoxysilane.
6. The epoxy resin adhesive based on an anti-settling thermal conductive network according to claim 1, characterized in that, The aramid nanofiber substrate is selected from one or more of poly(m-phenylene isophthalamide) and poly(p-phenylene terephthalamide).
7. The epoxy resin adhesive based on an anti-settling thermal conductive network according to claim 1, characterized in that, The thermally conductive filler is selected from one or more of silicon carbide whiskers, silicon carbide particles, and boron nitride.
8. A method for preparing an epoxy resin adhesive based on an anti-settling thermally conductive network as described in any one of claims 1-7, characterized in that, Includes the following steps: Preparation of MWCNTs / ANFs composite material: Aramid nanofibers and multi-walled carbon nanotubes were added to a mixed system containing a strong alkaline reagent, deionized water, and a polar aprotic organic solvent, and stirred to obtain a MWCNTs / ANFs mixed dispersion; then deionized water was slowly added dropwise to the mixed dispersion to induce the aramid nanofibers and multi-walled carbon nanotubes to settle and precipitate together, and the MWCNTs / ANFs composite material was obtained by filtration; Surface modification of filler: Prepare an ethanol-water solution, add silane coupling agent and stir to mix evenly to form a silane coupling agent hydrolysate; weigh the thermally conductive filler and add it to the silane coupling agent hydrolysate for dispersion treatment; filter the treated dispersion and vacuum dry to obtain the surface-modified thermally conductive filler. Preparation of thermally conductive composite material: Epoxy resin compound, multifunctional epoxy resin diluent, and MWCNTs / ANFs composite material are mixed and stirred until uniform. Then, surface-modified thermally conductive filler is added and dispersed evenly. Finally, curing agent is added and heated to cure, thus obtaining thermally conductive epoxy composite material.
9. The method for preparing the epoxy resin adhesive based on the anti-settling thermal conductive network according to claim 8, characterized in that, Includes the following steps: Preparation of MWCNTs / ANFs composite material: Aramid nanofibers and multi-walled carbon nanotubes were added to a mixed system containing potassium hydroxide, deionized water and dimethyl sulfoxide, and stirred at 40℃~60℃ for 2h~6h to obtain MWCNTs / ANFs mixed dispersion. Surface modification of filler: Prepare an ethanol-water solution, adjust the pH to 4.0~4.5, add silane coupling agent and stir to mix evenly to form a silane coupling agent hydrolysate; weigh the thermally conductive filler and add it to the silane coupling agent hydrolysate for dispersion treatment, and perform the following dispersion treatments in sequence: magnetic stirring for 20min~40min, high-speed homogenization for 15min~30min, and ultrasonic dispersion for 20min~40min; Preparation of thermally conductive composite material: Epoxy resin compound, multifunctional epoxy resin diluent, and MWCNTs / ANFs composite material are mixed and stirred at 70℃~80℃ until uniform. Then, surface-modified thermally conductive filler is added, ultrasonically treated to disperse uniformly, and finally, curing agent is added and heated to cure, thus obtaining thermally conductive epoxy composite material.